Clinical Evaluation of Humira® Biosimilar ONS-3010 in Healthy Volunteers: Focus on Pharmacokinetics and Pharmacodynamics - Dillingh, Marlous R.; Reijers, Joannes A. A.; Malone, Karen E.; Burggraaf, Jacobus; Bahrt, Kenneth; Yamashita, Liz; Rehrig, Claudia; Moerland, Matthijs (Frontiers in Immunology, 2016)
ONS-3010 is being developed by Oncobiologics Inc. (Cranbury, NJ, USA) as a biosimilar of Humira®. This randomized, double blind, single-center phase I study (EudraCT registration # 2013-003551-38) was performed to demonstrate pharmacokinetic biosimilarity between two reference products (Humira® EU and US) and ONS-3010 in healthy volunteers, and to compare the safety and immunogenicity profiles. In addition, the intended pharmacological activity was assessed and compared by application of a whole blood challenge. Hundred-ninety-eight (198) healthy volunteers received a single 40 mg subcutaneous dose of ONS-3010, Humira® EU or US. The pharmacodynamic effects were assessed by LPS/aluminium hydroxide whole blood challenges (n=36; n=12 per treatment arm; male:female, 1:1). Equivalence was demonstrated on the pharmacokinetic endpoints (AUC0-inf, Cmax and AUC0-last) based on bounds of 80-125% for the ratio of the geometric means (ONS-3010/Humira®). The immunogenicity profiles were comparable between treatment groups and there were no indications for differences in routine safety parameters. Administration of adalimumab resulted in the observation of dramatically reduced TNFα levels upon stimulation with LPS/aluminium hydroxide (> 99%), with no differences between the three treatment groups in terms of magnitude or duration Adalimumab also resulted in a reduction of LPS/aluminium hydroxide-induced IL-8 release (maximally 30%), suggested to have a causal relationship with the anti-TNFα treatment. LPS/aluminium hydroxide-induced release of IL-1β and IL-6 was not inhibited by anti-TNFα treatment. Taken together, these data are promising for the further clinical development of ONS-3010, demonstrate the relevance of the LPS/aluminium challenge to monitor Humira® effects, and emphasize the value of whole blood challenges for monitoring of proximal drug effects in healthy volunteers, and potentially in the target population.